Application of Erned Value Analysis Method on Building Rehabilitation and Renovation Project Works Iain Library and Laboratory, Sirimau District, Ambon City - Lestaluhu, Rusly; Serang, Rudi (International Journal of Advanced Engineering Research and Science, 2022)
In one construction project, overall cost and time control is part of construction management. By applying the Earned Value method, cost control and completion time can be done well. Thus avoiding cost and time, project control can be carried out properly in terms of time and cost. The results of this study are to determine the cost and time aspects of project performance each month and predict the costs and time to be able to complete the rest of the work so that corrective actions will be taken next. The results of the analysis of the Rehabilitation and Renovation Work of the Library and Laboratory Building of IAIN Sirimau District, Ambon City, the SPI value at week 16 was 1.04 or (>1) while the CPI was 1.05 or (>1) which means the project was implemented more faster than planning on a smaller budget. ETC value of IDR. 20,831,175,738 and the EAC value of IDR. 31,160,101,437.